Serum‐free culture alters the quantity and protein composition of neuroblastoma‐derived extracellular vesicles. Issue 1 (27th May 2015) - Li, Jinghuan; Lee, Yi; Johansson, Henrik J.; Mäger, Imre; Vader, Pieter; Nordin, Joel Z.; Wiklander, Oscar P. B.; Lehtiö, Janne; Wood, Matthew J. A.; Andaloussi, Samir EL
Abstract : Extracellular vesicles (EVs) play a significant role in cell–cell communication in numerous physiological processes and pathological conditions, and offer promise as novel biomarkers and therapeutic agents for genetic diseases. Many recent studies have described different molecular mechanisms that contribute to EV biogenesis and release from cells. However, little is known about how external stimuli such as cell culture conditions can affect the quantity and content of EVs. While N2a neuroblastoma cells cultured in serum‐free (OptiMEM) conditions did not result in EVs with significant biophysical or size differences compared with cells cultured in serum‐containing (pre‐spun) conditions, the quantity of isolated EVs was greatly increased. Moreover, the expression levels of certain vesicular proteins (e.g. small GTPases, G‐protein complexes, mRNA processing proteins and splicing factors), some of which were previously reported to be involved in EV biogenesis, were found to be differentially expressed in EVs under different culture conditions. These data, therefore, contribute to the understanding of how extracellular factors and intracellular molecular pathways affect the composition and release of EVs.